THE STATE AND PROSPECTS OF KAZAKHSTAN TRANSPORT COMPLEX DEVELOPMENT - Alpysbaiev, S. A.; Satova, R. K.; Mukhambetov, D. H.; Mukhambetova, A. D. (Science and Transport Progress, 2007)
On the basis of processing the statistical data the analysis of a technical condition and results of transportation activity of a transport complex ofKazakhstanis lead to the period with 2000 for 2006. Principal causes of a high share of a transport component in structure of gross national product of Kazakhstanare revealed and ways of its decrease are shown.